2014
DOI: 10.1136/bcr-2014-207559
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic aneurysmal giant right atrial enlargement with thrombus formation

Abstract: A 12-year-old boy presented to our outpatient department with progressive dyspnoea and palpitations of 6-month duration. Cardiovascular system examination revealed a short ejection systolic murmur at the left lateral heart border. Chest X-ray showed gross cardiomegaly. Two-dimensional ECHO revealed massive aneurysmal right atrial (RA) enlargement, low-pressure tricuspid regurgitation and dysplastic tricuspid valve with compression of the left atrium (LA) and left ventricle (LV). Cardiac CT showed grossly enlar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Some authors report non-specific findings such as tiny atrial tissue, as well as nonspecific muscular changes such as elongation of the fibres, lipomatous degeneration, lymphocytic infiltration, and patch fibrosis. 17,18,23 The finding of inflammatory tissue in some samples suggested myocarditis as a possible cause, 1 although this was only detected in isolated cases. In our series, the patient in whom we performed a histopathological study showed non-specific elements, which, consistent with the literature, did not prove useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors report non-specific findings such as tiny atrial tissue, as well as nonspecific muscular changes such as elongation of the fibres, lipomatous degeneration, lymphocytic infiltration, and patch fibrosis. 17,18,23 The finding of inflammatory tissue in some samples suggested myocarditis as a possible cause, 1 although this was only detected in isolated cases. In our series, the patient in whom we performed a histopathological study showed non-specific elements, which, consistent with the literature, did not prove useful.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Treatment is controversial in asymptomatic patients, especially in children. Prophylactic antiplatelet treatment has been suggested to prevent the risk of thrombus formation, 18 and surgical reduction has been performed in some symptomatic patients or in asymptomatic patients at high risk of progression, including initial severe right atrial dilatation, significant enlargement over a short period, compression of adjacent structures, or uncontrolled arrhythmias. 7 We present four cases of foetal diagnosis of idiopathic dilatation of the right atrium and discuss management from foetal to early postnatal life and follow-up until the patients reached the age of 5 to 6 years.…”
mentioning
confidence: 99%
“…1 Such aneurysms are rare, with their natural history complicated by death, heart failure, arrhythmias, and thrombosis. 2,3 Sporadic cases have been reported for all ages, from newborns to patients aged 75 years. 2 Diagnosis during childhood is quite rare, and prenatal diagnosis even rarer.…”
Section: Introductionmentioning
confidence: 99%
“…A histological section demonstrated primarily layers of collagen and smooth muscle cells with interspersed islands of atrial myocytes. 5 It is important to distinguish this anomaly from other cause of right atrial dilation especially tricuspid valve dysplasia and Ebstein anomaly. Most patients are asymptomatic with some presenting with atrial arrhythmias or thrombus formation.…”
mentioning
confidence: 99%
“…Most patients are asymptomatic with some presenting with atrial arrhythmias or thrombus formation. 5 It is important to distinguish this anomaly from other cause of right atrial dilation especially tricuspid valve dysplasia and Ebstein anomaly. Surgical resection, anticoagulation, catheter-based ablation, and watchful waiting…”
mentioning
confidence: 99%